A Review of Stratigraphic Foward Models (Sfm) for Carbonate Platform - Rosli, Redwan; Poppelreiter, Michael C.; Jamaludin, Siti Nur Fathiyah (International Journal of Engineering and Technology, 2018)
Stratigraphic forward modelling (SFM) is a numerical method that simulates the key factors that control depositional processes. A few models have been developed over years for different geological environment (fluvial, turbidite and carbonate). The model for carbonate system is particularly more complex compared to others. This is due to fact that carbonate system is controlled by the interplay between carbonate productivity, eustasy, subsidence/uplift. Carbonate platform’s morphology also strongly influenced by hydrodynamic factors (Wind and Waves). SFM has been used to test the hypothesis on factors that controlled the evolution of carbonate platforms. This technique also a reliable tool for hydrocarbon exploration and development. SFM has been used to predict carbonate facies distribution, petrophysical properties, and architecture of carbonate platforms. In this review paper, four SFMs namely CARB3D+, GPM CARBONATE, DIONISOS, SEDPAK are discussed.
Keywords: carbonate platform; hydrocarbon exploration tool; stratigraphic forward model (SFM)